Molecular Identification of Methylorubrum extorquens using PCR-Amplified MxaF Gene Fragments as A Molecular Marker (Baghdad Science Journal, 2024)
Methylotrophs bacteria are ubiquitous, and they have the ability to consume single carbon (C1) which makes them biological conversion machines. It is the first study to find facultative methylotrophic bacteria in contaminated soils in Iraq. Conventional PCR was employed to amplify MxaF that encodes methanol dehydrogenase enzyme. DNA templates were extracted from bacteria isolated from five contaminated sites in Basra. The gene specific PCR detected Methylorubrum extorquens as the most dominant species in these environments. The ability of M. extorquens to degrade aliphatic hydrocarbons compound was tested at the laboratory. Within 7 days, gas chromatographic (GC) studies of remaining utilized crude oil revealed that 61.14 % of the initial content had been degraded, and GC fingerprinting of the utilized aliphatic compounds revealed significant reductions in C12, C13, C14, and C15. Globally this is the first time found a new strain of   M. extorquens has the ability to degrade aliphatic hydrocarbons compound. Conventional PCR and gene sequencing revealed the presence of the facilitative methylotrophic bacteria in polluted areas in Basra. M. extorquens was dominant and showed a substantial ability to degrade crude oil which makes them an important tool to be employed in bioremediation.